Leaching of CEM III paste by demineralised or mineralised water at pH 7 in relation with aluminium release in drinking water network. (May 2021) - Berthomier, Mathilde; Lors, Christine; Damidot, Denis; De Larrard, Thomas; Guérandel, Cyril; Bertron, Alexandra
Abstract: Drinking water pipes can be lined with a cement matrix based on CEM III, which can release aluminium into the water. However, the European Union limits the aluminium concentration in drinking water for public health reasons. In order to study the long-term leaching mechanism of aluminium, semi-dynamic leaching tests using an aggressive solution (demineralised water) or drinking water (mineralised water) were conducted on crushed CEM III pastes maintained at pH 7. They resulted in a very high leaching coefficient, approaching 50%. However, in spite of this strong leaching, the amount of Al leached remained very low, at less than 1.5% of the initial amount of Al in the material. Under these conditions, the leaching of Al from a CEM III paste is complex since it involves several steps, where slag (1st and last steps) or cement paste (2nd step) are the main contributors.